Clinical research priorities in emergency medicine: Results of a consensus meeting and development of a weighting method for assessment of clinical research priorities. (February 2014) - Thom, Ogilvie; Keijzers, Gerben; Davies, Suzanne; McD Taylor, David; Knott, Jonathan; Middleton, Paul M
Abstract Introduction There is limited evidence regarding clinical research priorities in emergency medicine outside of some special interest groups. The ACEM Clinical Trials Group undertook a consensus meeting with the aim of developing a reproducible weighting matrix for assessing clinical research priorities. Methods A session at the ACEM annual scientific meeting was dedicated to this meeting. Results from a survey of the ACEM researcher database were presented, along with a proposed weighting matrix. After discussion and adjustment, consensus was achieved on the matrix. Results It was agreed that the following criteria be used in the matrix: research category and sub‐category priority ranking from the ACEM researcher database survey, frequency of presentation of potentially eligible participants, the level of pre‐existing evidence regarding the proposed research question and the likely clinical impact of the research. Each criterion was given a weighting, with clinical impact given the heaviest weighting. The weighting matrix was subsequently applied to the list of research questions that resulted from the researcher database survey and a list of research priorities determined. Conclusion The weighting matrix allows reproducible comparison of research questions. The resultant list of research priorities will act as a guide for the ACEM Clinical Trials Group in determining future projects.